METAMORPHISM OF PALEOPROTEROZOIC PARAGNEISSES IN THE BELARUS-PODLYASIE GRANULITE BELT: PROGRADE-RETROGRADE EVOLUTION - Taran L.N.; Bogdanova S.V. (My University, 2003)
Metasedimentary granulites from the central portion of the Belarus-Podlyasie granulite belt were studied with the purpose to reproduce the Paleoproterozoic tectono-thermal evolution in the western part of the East European craton. The regularities identified in the compositional variations in minerals (particularly, garnet), textural relations between minerals, and thermobarometric data point to the complicated evolution of metamorphism with a well pronounced prograde stage. The latter is marked by the predominantly growth zoning of large garnet poikiloblasts from the paragneisses and corresponding variations in the composition of biotite and plagioclase inclusions in this garnet, which testify, when analyzed together with textural-structural relationships between minerals, to a temperature and pressure increase from 530-570°C, 3-4 kbar to 650-670°C, 6-7 kbar at ∼1870 Ma. The metamorphic peak is represented by the assemblages Grt ± Crd + Sil + Bt ± Spl ± Ilm + Mag + PI + Kfs + Qtz, occurred at T = 750-760°C, P = 7.5-8 kbar, at t ∼ 1800 Ma and was coeval with intense bimodal magmatism during the postcollisional evolutionary stage of the granulite belt. Retrograde reactions proceeded as the temperature and pressure decreased from their peak values to 530-540°C, 3.5-4.5 kbar at 1780-1740 Ma. The fairly high uplift velocities and cooling rate of the rocks (1.4-0.2 mm/yr and 20-4°C/m.y., respectively), the preservation of garnet growth zoning, and a characteristic configuration of the P-T-t path suggest the relatively rapid exhumation of the granulites to upper crustal levels.
Keywords: Paleoproterozoic; Precambrian::Proterozoic::Paleoproterozoic; Докембрий::Протерозой::Палеопротерозойская